Hubungan rasa memiliki pada organisasi dan konformitas terhadap partisipasi perempuan dalam sekaa teruna teruni di Bali - Widiyasari, Ni Komang Tri Utami; Suarya, Luh Made Karisma Sukmayanti (Jurnal Psikologi Udayana; Vol 9 No 1 (2022)DO - 10.24843/JPU.2022.v09.i01.p10, 2022)
Sekaa Teruna Teruni (STT) is one of the youth organizations in Bali. The achievement of the goals of STT is influenced by various factors, one of which is the participation of organizational members which can arise due to a sense of belonging and conformity. STT membership, which is generally voluntary, causes almost no pressure requiring STT members to be present and active in STT activities, but when viewed from the daily activities in STT, there is a tendency that men take more roles than women. This research is a quantitative study that aims to determine the relationship between a sense of belonging in an organization and conformity, with women's participation in the STT. Sampling was done by cluster random sampling with a total sample of 178 female members who attended STT in Badung, Tabanan, and Gianyar districts. The measuring instrument used in this study consists of three scales, namely, Participation in the STT scale, Sense of Belonging scale, and Conformity scale. The data analysis technique used in this research is multiple correlation test. Based on the analysis of the hypothesis test, the correlation coefficient value is 0.653 with F count as 65,118 and significance 0,000 (p<0,005) which indicates a relationship between a sense of belonging to the organization and conformity with women's participation in STT. The higher the sense of belonging to the organization and conformity, the higher the level of women's participation in STT.